Case report: intravascular ultrasound sonography-guided re-entry technique in crushed stent. Issue 2 (6th March 2020) - Iannaccone, Mario; Barbero, Umberto; De Benedictis, Michele; D'ascenzo, Fabrizio
Abstract: Background: Stent thrombosis (ST) is a rare, but potentially fatal complication. Procedural problems, such as stent under-dimension/under-expansion or dual antiplatelet drug resistance may result into ST. These conditions are more frequent during primary percutaneous coronary intervention for ST-elevation myocardial infarction (STEMI). Case summary: A 60-year-old male patient presented to our hospital with an inferior STEMI. In the emergency department, a dual antiplatelet therapy was administered with ticagrelor 180 mg and aspirin 250 mg IV. During the observation, the patient experienced a ventricular fibrillation. Urgent coronary angiography showed an occlusion of the proximal right coronary artery. Thrombus aspiration was performed followed by implantation of one drug-eluting stent. After 45 min early ST occurred and was treated by immediate thrombus aspiration and post-dilatation. Intravascular ultrasound sonography (IVUS) showed severe strut malapposition due to a partial crush after post-dilatation. Since it was not possible to directly insert the first guidewire in the stent lumen, the IVUS probe was placed between the vessel wall and the crushed stent to guide the manoeuvre. Discussion: Crushed stent is a rare complication, being caused by an incorrect passage of the guidewire between the stent's struts and the vessel wall in case of severe underexpansion. In this case, an IVUS-guided re-entry could be an option to gain the stent true lumen and avoid a second stent implantation.